INOVASI MEDIA PEMBELAJARAN ONLINE DALAM PEMBELAJARAN PAI DI MAN 1 KOTA MALANG - Diana Haris Mayansari Agustina; Muhammad Hanif; Moh. Muslim (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Learning during the COVID-19 pandemic is done online by utilizing developed technology. A teacher in online learning activities serves as a facilitator and innovator to determine the model or media that will be used during learning. This research is a research related to online learning media innovations carried out by PAI MAN 1 Malang City teachers during the covid-19 pandemic. This research focuses on online learning media innovation, its implementation, and the impact of online learning media. While the purpose of this study is to find out the innovations of learning media used by PAI teachers in online learning and their implementation, and the obstacles they experience. The research method used is qualitative with the type of case study research. Collecting data using observation, interviews, and documentation. The results of this study indicate that the learning media innovation used by PAI MAN 1 Malang City teachers is e-learning from the Ministry of Religion, Zoom, Wa grub, and others. And the state of motivation of class XI MAN 1 Malang City students in online learning has decreased, so PAI teachers have to use other efforts to keep growing student motivation.